Towards optimizing the timing of the pre-exercise meal - Maffucci, D. M.; McMurray, R. G. (International Journal of Sport Nutrition and Exercise Metabolism, 2000)
Summary This article takes a comparative look at an athlete¡¯s performance after eating 6 hours and 3 hours before exercise. The theory is that eating 6 hours before exercise is similar to inducing a 6-hour fast, the effects of which can be similar to those of a 12-hour fast. The study involved eight females, ranging from 18 to 30 years of age. All of the women were training for collegiate teams of triathlons and had been exercising at least 5 days/week for at least 3 months. For the 6-hour pre-exercise trial, each athlete ate a 55%-carbohydrate/ 25%-fat/ 20%-protein breakfast with calories based on her body weight 6 hours prior to testing. If the athlete was being tested for the 3-hour pre-exercise trial, she also ate a 60% carbohydrate/20% fat/20% protein lunch and reported to the lab for testing exactly 3 hours after eating it. Exercise was designed to mimic a typical training session, including 30 minutes at a heart rate of 150 bpm with 30-second sprints every five minutes. At the end of 30 minutes, intensity was increased every 2 minutes until the subject could no longer perform the activity. This was the high-intensity time to exhaustion Results The comparison demonstrated that the athletes did not perform as well after the 6-hour fast as they did when they ate their meal 3 hours before the exercise. During the 6-hour trial, they were using more fats than during the 3-hour trial. Even though their levels of blood glucose were higher for the 6-hour trial, they were not utilizing it. Fat is not an efficient energy source for high-intensity work. This probably explains why performance of the high-intensity time to exhaustion was reduced 11% with the 6-hour trial compared to the 3-hour trial. Implications Moderate-duration, high-intensity exercise, such as swimming workouts, should be proceeded by a moderate-sized meal eaten 3 hours in advance versus 6 hours. Fasting as little as 6 hours can have a negative impact on performance, both day-to-day and in competition.